Color and shape reversible, recoverable and repeatable mechanochromic shape memory polycaprolactone: a single material with dual functions. Issue 1 (29th November 2019) - Yenpech, Nattawat; Intasanta, Varol; Tashiro, Kohji; Chirachanchai, Suwabun
Abstract : A polycaprolactone-based mechanochromic shape memory material exhibits reversible and repeatable shape and color as a result of its crystallinity. Abstract : Mechanochromic polymers develop their color when the stretching force leads the mechanophores to change their molecular structure or configuration. However, shape memory polymers maintain their original shapes because of the balance of switching segment and net-point after a particular thermal treatment. Polymers with both mechanochromic and shape memory, hereinafter called mechanochromic shape memory, and defined as being color/shape reversible, recoverable, and repeatable materials, have not yet been reported. This type of the material is useful because the color change indicates the material breakage and it can recover after the treatment. The present work shows a molecular design and synthesis of a single-polymer system to perform mechanochromic shape memory by incorporating a spiropyran mechanophore molecule (SP) onto the linear backbone of thermoplastic poly(caprolactone) (PCL) (switching segment) and further chemically crosslinking it on to a four-armed PCL (net-point). The systematic variations related to the linear PCL chain lengths (molecular weight), the amount of PCL branches (net-point) and the SP contents together with microstructure analyses lead us to understand that the stretching force applied to the material has to be sufficient for not only aligning the linear PCL from the low ordered switching segments to the high ordered switching segments, but also inducing transformation from spiropyran to merocyanine. The present work, for the first time, shows the dual functions in a single PCL system as a model example of a mechanochromic shape memory material.